Phosphorylation mediated regulation of RNA splicing in plants - Rodriguez Gallo, Maria Camila; Uhrig, R. Glen (Frontiers in Plant Science, 2023)
For the past two decades, the study of alternative splicing (AS) and its involvement in plant development and stress response has grown in popularity. Only recently however, has the focus shifted to the study of how AS regulation (or lackthereof) affects downstream mRNA and protein landscapes and how these AS regulatory events impact plant development and stress tolerance. In humans, protein phosphorylation represents one of the predominant mechanisms by which AS is regulated and thus the protein kinases governing these phosphorylation events are of interest for further study. Large-scale phosphoproteomic studies in plants have consistently found that RNA splicing-related proteins are extensively phosphorylated, however, the signaling pathways involved in AS regulation have not been resolved. In this mini-review, we summarize our current knowledge of the three major splicingrelated protein kinase families in plants that are suggested to mediate AS phosphoregulation and draw comparisons to their metazoan orthologs. We also summarize and contextualize the phosphorylation events identified as occurring on splicing-related protein families to illustrate the high degree to which splicing-related proteins are modified, placing a new focus on elucidating the impacts of AS at the protein and PTMlevel.